2004
DOI: 10.1038/sj.ejcn.1601947
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of habitual meal pattern and intake of foods, energy and nutrients in Swedish adolescent girls: comparison of diet history with 7-day record

Abstract: Objective: To compare the diet history (DH) method to an estimated 7-day record (7-d) concerning meal pattern and intake of foods, energy and nutrients. Design: After the DH interview, subjects completed the 7-d. Setting: School setting, Göteborg, Sweden. Subjects: A total of 51 adolescent girls (15-16 y) recruited from 634 girls participating in The Göteborg Adolescence Study. Results: Two-thirds of the girls had identical or similar main meal pattern, while the number of in-between meals was higher using DH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
5
15
0
2
Order By: Relevance
“…Furthermore, the tendency to underestimate foods perceived as socially undesirable may contribute to lower estimates of pastries (e.g., cakes, cookies, pies, and spicy snacks). This is in accordance with other studies: van Liere et al [29] revealed a lower consumption of cakes with diet history questionnaires in comparison with 24-h recalls and Sjöberg-Hulthen et al [28] found a lower consumption of sweet baked goods with the diet history questionnaire than with food records. Table 7 Food consumption of underreporters and plausible reporters and relative differences between these for each dietary assessment method In general, the results show that inhomogeneous food groups are more difficult to assess and show lower accordance between different dietary assessment methods.…”
Section: Comparison On the Level Of Food Consumptionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the tendency to underestimate foods perceived as socially undesirable may contribute to lower estimates of pastries (e.g., cakes, cookies, pies, and spicy snacks). This is in accordance with other studies: van Liere et al [29] revealed a lower consumption of cakes with diet history questionnaires in comparison with 24-h recalls and Sjöberg-Hulthen et al [28] found a lower consumption of sweet baked goods with the diet history questionnaire than with food records. Table 7 Food consumption of underreporters and plausible reporters and relative differences between these for each dietary assessment method In general, the results show that inhomogeneous food groups are more difficult to assess and show lower accordance between different dietary assessment methods.…”
Section: Comparison On the Level Of Food Consumptionsupporting
confidence: 91%
“…Mean food consumption assessed with the diet history questionnaire gave higher estimates for three of the 18 food groups compared with the weighed food records in men and for one food group in women. Sjöberg and Hulthen [28] compared results of a diet history questionnaire with an estimated 7-day food record from 51 girls 15-16 years of age. For most food groups (14 out of 20) they showed higher consumption assessed with the diet history questionnaire in comparison with food records.…”
Section: Comparison On the Level Of Food Consumptionmentioning
confidence: 99%
“…General overview An overview of the retrieved twenty original articles (1,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) is shown in Table 1.…”
Section: Original Articlesmentioning
confidence: 99%
“…The majority (n 17) (1,(13)(14)(15)(16)(17)(18)(19)(20)(22)(23)(24)26,27,(29)(30)(31) of them were identified as studies assessing the validation and reproducibility of FFQ against reference dietary instruments (Table 2), while the remaining three studies considered questionnaires other than FFQ analysed for their validity and reproducibility against different reference methods (21,25,28) ( Table 3). …”
Section: Original Articlesmentioning
confidence: 99%
See 1 more Smart Citation